Building material stocks and embodied carbon dataset for two urban agglomerations in China from 2000 to 2020 - Hanwei Liang; Baizhe Zhang; Xuepeng Qian; Ying Chen; Ye Luo; Yujin Huang; Lu Sun; Chen Zhou; Jie Long; Liang Dong (Scientific Data)
Abstract Built environment is critical for net zero transition. Urban agglomerations, characterized by dense concentrations of buildings, significantly contribute to these emissions. Therefore, it is critical to analyze and manage embodied carbon emissions (ECE) from buildings across all lifecycle stages. Notably, the “cradle to gate” stage, spanning from raw material extraction to product manufacturing, accounts for the majority of total lifecycle emissions. This study provides comprehensive data inventories of material stocks and associated embodied carbon emissions for the cradle-to-gate stage in China’s two major urban agglomerations: the Yangtze River Delta (YRD) and the Greater Bay Area (GBA). The dataset provides data, theoretical foundation and application scenarios for further research. By providing a comprehensive dataset and valuable technical support for future research in carbon mitigation strategies, this study contributes to global efforts to meet the carbon reduction targets established by the Paris Agreement. It lays the groundwork for informed urban planning and environmental policy, facilitating detailed, longitudinal analyses of building materials and their carbon footprints, which are crucial for sustainable development.